Lecture I: Musical forming - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2007)
Lecture I: Musical Forming given on February 13th 1972 at the Institute of Contemporary Arts, London.Excerpts from KONTRA - PUNKTE, GRUPPEN, GESANG DER JÜNGLINGE, ZEITMAßZE,ZYKLUS, KREUZSPIEL, MANTRA, CARRÉ.